Fairy tales through the eyes of Angela Carter. - Ng, Melissa Shu Ting. (2009)
Once upon a time in a faraway land” and “they lived happily ever after” are words that signify the beginning of a magical journey which is not complete without the appearance of archetypal symbols such as the beautiful princess or the poor pitiful girl, the gallant prince, the usual group of monsters, a villain which usually takes the form of a wicked stepmother, animals that speak as well as the “expected” ending whereby the hero (prince) sweeps the princess off her feet and rides with her on his snow white stallion, away into the horizon. Such is the experience that many of the modern fairy tales have tried to convey to their present audience, creating a dream-like landscape for the readers to be lost in. Some of these famous fairy tales which have enthralled and mesmerise many, monopolising hours of each individuals include “Snow White”, “Sleeping Beauty”, “Cinderella”, “Beauty and the Beast”, “Little Red Riding Hood” and many more. However, People have become frustrated with this limited manner of thinking and assumption which subsequently leads to the abandonment of that impractical way of thinking and indulgence for realism and practicality. However, this magical dream which have captivated many seemed more like a broken down recorder that kept on playing the same repetitive compulsion that have shrouded the traditional fairy tale, turning it into a burden and a delusion as opposed to the once “ideal” world that everyone desires and craves for. Angela Carter tries to bring back the delight that one used to have in reading the fairy tales, taking this opportunity to re-new, revise, recreate and rework the entire body of the fairy tale. Like a kaleidoscope, she fragments the structure of the traditional fairy tales whilst reviving and revitalising the text as well as the reader through the use of juxtaposing the world of realism which the reader is used to a world whereby the reality is governed by the laws of dreams, myth and magic. She strips the fairy tale bare of all pretence and packaging, thus allowing the readers to attain true enjoyment and understanding of the fairy tale, “She opens an old story for (the readers), like an egg and finds the new story, the now story (that) we want to hear, within.” (Rushdie, “Burning your Boats; The Collected Short Stories, P.g14).